Innate immune defenses in HIV-1 infection: prospects for a novel immune therapy (2006)
ABSTRACT: HIV-1 infection leads to a severe decrease of CD4+ T lymphocytes, dysregulation of several leukocyte subpopulations and generalized immune activation, with the subsequent development of opportunistic infections and malignancies. Administration of highly active antiretroviral therapy (HAART) has been successful in reducing HIV-1 plasma viremia; however, the ability of HAART to restore immunocompetence appears incomplete, particularly in patients with chronic and advanced disease. Several components of the innate immune system have direct anti-HIV-1 effects, and studies to analyze the benefits of enhancing the function of the innate response during HIV-1 infection are increasing. Development of any complementary therapeutic approaches to HIV-1 infection, particularly those able to compensate for the limitations of HAART, and enhance the anti-HIV-1 innate immune activity would be of interest. The stimulation of innate immune responses using Toll-like receptor agonists, such as monophosphoryl lipid A and oligodeoxynucleotides with CpG motifs, are currently being investigated and their benefit in HIV-1-infected patients are under evaluation.